Introducing positive psychology to SLA - Mercer, Sarah; MacIntyre, Peter D. (Studies in Second Language Learning and Teaching, 2014)
Positive psychology is a rapidly expanding subfield in psychology that has important implications for the field of second language acquisition (SLA). This paper introduces positive psychology to the study of language by describing its key tenets. The potential contributions of positive psychology are contextualized with reference to prior work, including the humanistic movement in language teaching, models of motivation, the concept of an affective filter, studies of the good language learner, and the concepts related to the self. There are reasons for both encouragement and caution as studies inspired by positive psychology are undertaken. Papers in this special issue of SSLLT cover a range of quantitative and qualitative methods with implications for theory, research, and teaching practice. The special issue serves as a springboard for future research in SLA under the umbrella of positive psychology.